Evaluación de diferentes tipos de sustratos en vivero de cacao (Theobroma cacao). - Defaz Quilumba, César Leonardo (2016)
This research was conducted at the experimental farm "La Maria" State Technical University of Quevedo, located at Km 7.5 Vía Quevedo - El Empalme, with the overall objective to determine the effect of different organic substrates on seedling growth cocoa nursery conditions. The specific objectives were to evaluate the growth of cocoa plants in different substrates study, identify the substrate that allows greater root development of seedlings of cacao and perform economic analysis of each of the treatments studied. The experiment was conducted under a completely randomized design with 10 treatments in three replicates and treatment means were compared with Duncan test at 95% probability. The treatments were: T1: 60% Bokashi + 40% black earth, T2: 60% Bokashi + 40% sawdust raft, T3: 60% Bokashi + 40% chaff burnt rice, T4: 40% Bokashi + 20% sawdust balsa + 20% black soil + 20% chaff burnt rice, T5: 60% vermicompost + 40% black earth, T6: 60% vermicompost + 40% sawdust raft, S7: 60% vermicompost + 40% chaff burnt rice, T8: 40% vermicompost + 20% black soil + 20% chaff burn rice + 20% sawdust raft, T9: 30% bokashi + 30% vermicompost + 20% black earth + 10% sawdust + 10% balsa burning rice chaff, T10: 75% + 25% black earth rice husks. The main results of this research it was observed that the planted in treating 9 (30% Bokashi, 30% vermicompost, 20% black soil, 10% sawdust balsa and 10% chaff burnt rice), was recorded 100% germination, plant also produced in this substrate were greater height, stem diameter, presence of leaves and root length. Treatment 10 (75% of black earth and 25% rice husks) produced the highest returns with 59.68% of the production of 1000 seedlings, meaning that for every dollar invested a profit of $ 0.60 was obtained for every dollar reversed, however, with treatment 9 (30% bokashi, 30% vermicompost + 20% black soil + 10% sawdust raft + 10% chaff burnt rice) plants showed better characteristics that are the basis for acceptance by the buyer, generating a return of 34.23%, as a result of higher production cost.